Perbaikan Kinerja Dwelling Time Di Terminal Peti Kemas KOJA di Pelabuhan Tanjung Priok - Ellenlies, Ellenlies; Siahaan, Langas Denny; Ayutia, Yolla; Andarini, Amelia; Kasenda, Muhammad Hiero Rio; Parhusip, Veronica (Institut Transportasi dan Logistik Trisakti, 2021)
The terminal is the main and most important element for serving, loading and unloading of goods. The services provided are in the form of loading and unloading activities, arranging and storing goods in the transit warehouse or at the stacking yard, receiving goods to be shipped or sent and handing over the goods to the consignee after being unloaded from the ship. The waiting time or time scale required for a container from the time it is unloaded or lifted from the ship's hold (unloading) until the container leaves the port is known as the dwelling time process. The process of determining the length of dwelling time at the port is Preclearance, Custom Clearance, and Post Clearance. Dwelling time service performance research was conducted at Koja Container Terminal with descriptive quantitative methods, with a total sample of 75 service users. Data collection was carried out by distributing questionnaires with a Likert scale model that had been tested. Then the data collected was analyzed using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The results of the study show that the value of the service user satisfaction index is75.29%, the level of conformity of dwelling time service performance has not met the expectations of service users, and the main priority for improving dwelling time service performance is 10 attributes that is included in quadrant A and 12 attributes have to be maintained in quadrant B.